DETERMINATION OF OXIDATIVE STRESS FACTORS IN PATIENTS WITH HEREDITARY MUSCLE DISEASES: ONE POSSIBLE DIAGNOSTIC AND OPTIONAL MANAGEMENT OF THE PATIENTS - NIRAJ KUMAR SRIVASTAVA; ACHAL KUMAR SRIVASTAVA; SOMANATH MUKHERJEE; ROHAN SHARMA; ASHOK KUMAR MAHAPATRA; DEEPAK SHARMA (International Journal of Pharma and Bio Sciences, 2015)
Superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT) and lipid peroxidation (LP) are familiar parameters for investigating the oxidative stress induced pathogenesis of hereditary muscle diseases. Results stated that oxidative stress may be hosting a role in the pathogenesis of hereditary muscle diseases. Evaluated defensive parameters (SOD, GPx & CAT) and indicative parameter (LP) are collectively considered as oxidative stress factors and represented the oxidative stress status of the patients. Alterations in the levels of these factors follow the uniform pattern in patients with muscular dystrophies and mitochondrial myopathies. These factors also provide the possibility for the development of alternate diagnostic method. On the basis of such informations, clinicians would be able to manage the patients with addition of appropriate antioxidants in the medication or diet. There is no permanent treatment for patients with hereditary muscle diseases and management of disease is a solitary option of delaying the deterioration progress.